Metacognition and general functioning in patients with schizophrenia and a history of criminal behavior. Issue 3 (28th February 2015) - Bo, Sune; Kongerslev, Mickey; Dimaggio, Giancarlo; Lysaker, Paul H.; Abu-Akel, Ahmad
Abstract: Metacognitive difficulties have been linked to social dysfunction in schizophrenia. However, research examining the role of metacognition in the social functioning of patients with a history of violence and criminality is very limited. This research is especially important for this group given their relatively poor prognosis and their risk to reoffend, as well as the promising benefits of integrating metacognitive approaches in psychosocial treatments. In this study, the association between metacognition and global social functioning was examined in 79 patients with schizophrenia with a criminal background. We also examined the association of positive, negative and disorganized symptoms with social functioning and the extent to which metacognition mediates this association. The results indicate that poor social functioning is associated with metacognitive difficulties and higher levels of delusions and Conceptual Disorganization. In addition, meditation analyses showed that metacognition accounted for about 11% of the total effect size of the association between delusions and social dysfunction, suggesting that the relationship between delusions and social dysfunction is partially driven by impaired metacognition. These findings underscore the importance of interventions designed to enhance the patients׳ metacognitive capacities, that is, the more proximal capacities linked to poorer social functioning. Highlights: Metacognition predicts social functioning in schizophrenia patients with criminal behavior. Positive symptoms predict social functioning in patients with criminal behavior. Metacognition mediates the link between delusions and social functioning.